(untitled) (Leviathan (São Paulo), 2014)
This article offers an interpretation, one among many other possible, of the Las Luchas de clases en Francia (1850) and El dieciocho brumario de Luis Bonaparte (1852). Our hypothesis is that in Marx’s political analysis politics are necessarily linked to representation and is unconceivable without it. Taking as the connecting thread the metaphor of the scenario used by Marx to understand politics, in the first part we scrutinize the books looking for the role of political action in dialogue with Marx’s economicist readings. Marx represents politics as a theater, but it doesn’t mean he demotes it to a secondary position. Although action is produced among constrains left from past and from the class conflicts, he does not overlook that it also has a considerable amount of contingency. In the second part, we examine what, keeping with metaphor, could be denominated the “characters” and their “scripts”, it means, the way Marx conceptualizes the subjects that are present in the political scene and the problems raised by the representation of their interests. These characters are the classes, the class’ frictions and the parties, defined both in relation to their objective interests and to their struggles. Amid these interests (scripts) and their representation, there is an hiatus, which makes representatives to have some room for manoeuvre to reformulate (improvise) interests according to power relationships. Consequently, such interests cannot be produced apart from the dynamic of representation